2018
DOI: 10.1007/s11302-018-9615-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P2X1 receptors in somatostatin-containing cells in mouse gastrointestinal tract and pancreatic islets of both mouse and human

Abstract: With immunohistochemical and Western blot techniques, P2X1 receptors were detected in the whole mouse gastrointestinal tract and pancreatic islets of mouse and human. (1) δ Cells containing somatostatin (SOM) in the stomach corpus, small intestines, distal colon, pancreatic islets of both mouse and human express P2X1 receptors; (2) strong immunofluorescence of P2X1 receptors was detected in smooth muscle fibers and capillary networks of the villus core of mouse intestine; and (3) P2X1 receptor-immunoreactive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the rat submucous plexus, SOM-positive neurons have been divided into two groups: those containing both CGRP and SP (60% of all neurons immunoreactive to SOM) and those containing only CGRP without SP [64]. In turn, the latest studies have shown the presence of chemokine CXCL 14 and P2X1 receptors in the SOM-positive nervous structures in the mouse digestive tract, which suggests that CXCL14 contributes to the function of somatostatin in the enteric neuron system and that ATP may participate in SOM release from the enteric neurons [72,73].…”
Section: The Presence Of Somatostatin (Som) In the Enteric Neuronsmentioning
confidence: 99%
“…In the rat submucous plexus, SOM-positive neurons have been divided into two groups: those containing both CGRP and SP (60% of all neurons immunoreactive to SOM) and those containing only CGRP without SP [64]. In turn, the latest studies have shown the presence of chemokine CXCL 14 and P2X1 receptors in the SOM-positive nervous structures in the mouse digestive tract, which suggests that CXCL14 contributes to the function of somatostatin in the enteric neuron system and that ATP may participate in SOM release from the enteric neurons [72,73].…”
Section: The Presence Of Somatostatin (Som) In the Enteric Neuronsmentioning
confidence: 99%
“…Oral treatment (Lactobacillus plantarum ys2) in carbon-induced constipation Kunming mice reduced serum SST level, promoted gastrointestinal peristalsis, and reduced the first black stool defecation time ( 54 ). SST immunoreactive neurons co-expressed with P2X1-receptor (ATP receptor) was detected in mouse myenteric and submucosal plexuses ( 55 ). Using intrinsic markers targeting vagal and spinal sensory, sympathetic, and parasympathetic axons, the spatiotemporal map showed extrinsic axons project along the myenteric plexus and keep intimate contact with enteric neurons in whole gut in mice E9.5-E16.5 ( 56 ).…”
Section: Sst-enteric Endocrine Cells and Nervous System In The Gastromentioning
confidence: 99%